THERMOLUMINESCENCE PROPERTIES OF THE 0.5P₂O₅ - xBaO - (0.5-x)K₂O GLASS SYSTEM. A POSSIBLE DOSIMETRIC MATERIAL - IVAȘCU, Cosmin; COZAR, I. B.; TIMAR-GABOR, A.; COZAR, O. (Studia Universitatis Babeș-Bolyai Physica, 2015)
Thermoluminescence (TL) properties of freshly b irradiated phosphate glasses doped with BaO and K2O oxides at various concentrations were investigated. Barium-doped glasses (0.5P2O5 - 0.5BaO) show two TL peaks centered at 180 0C and 380 0C due to the defects generated by modifier Ba2+ ions inserted into the glass network. In the case of potassium-doped glasses (0.5P2O5 - 0.5K2O) an intense TL peak at 280 0C with an weak shoulder at 150 0C appear. The TL emission of the other phosphate glasses, 0.5P2O5 - xBaO - (0.5-x)K2O with 0.1 £ x £ 0.4, containing both type of the network modifier ions (K+, Ba2+) consist from the overlap of the above – mentioned luminescence spectra depending on the local energetic level diagrams of the luminescence centers. A linear dependence (R2 > 0.99) of the integral TL signals with the absorbed doses were evidenced for all the investigated glasses which can be considered as good materials for dosimetry in the 0 – 50 Gy range.